Design for Electromagnetic Compatibility--In a Nutshell Theory and Practice - Keller, Reto B. (Springer International Publishing : Imprint: Springer, 2023)
This open access book provides practicing electrical engineers and students a practical - and mathematically sound - introduction to the topic of electromagnetic compatibility (EMC). The author enables readers to understand better how to overcome commonly failed EMC tests for radiated emission, radiated immunity, and electrostatic discharge (ESD), while providing concrete EMC design guidelines. The book also presents an overview of EMC standards and regulations and how to test for a global market access. Provides a state-of-the-art introduction to EMC for students and practicing engineers Covers the essential theoretical topics for mastering EMC Gives general practical advice on how to design EMC compliant electronics.